The Concept of Qudwah and its Implications for Teacher Personality Competence in Islamic Education - Saepurrohman, Aep; Erihadiana, Mohamad (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
This study explores the concept of “qudwah” in Islamic education and its relevance to teacher personality competence, particularly regarding role modelling. The research focuses on the crucial role of teachers in education, where role modelling is considered a key indicator of personality competence. In Islamic education, “qudwah” refers to the exemplary behaviour teachers should embody, significantly influencing students. The methodology is a literature review, analyzing primary and secondary sources related to “qudwah” and teacher personality competence. This research aims to elucidate the meaning and application of the “qudwah” concept and assess its implications for teacher personality competence. The findings reveal that “qudwah” dramatically impacts students’ perceptions and emulation of their teachers. Good role modelling by teachers reinforces educational values and aids in students’ character development. The implications of these findings underscore the need to integrate the “qudwah” concept into teacher training and professional development to enhance personality competence. Recommendations from this study include improving the understanding and application of the “qudwah” concept within education curricula and teacher training programs so that teachers can provide effective role models and create a more inspiring and productive educational environment. This research contributes not only theoretically but also practically to supporting and strengthening the role of teachers as the main pillar in quality education, particularly in the context of Islamic education.